2019 European Conference on Networks and Communications (EuCNC) 2019
DOI: 10.1109/eucnc.2019.8801986
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Polarization Diversity in Massive MIMO for Industry 4.0

Abstract: The massive polarimetric radio channel is evaluated in an indoor industrial scenario at 3.5 GHz using a 10×10 uniform rectangular array (URA). The analysis is based on (1) propagation characteristics like the average received power and the power to interference ratio from the Gram matrix and (2) system-oriented metrics such as sum-rate capacity with maximum-ratio transmitter (MRT). The results clearly show the impact of polarization diversity in an industrial scenario and how it can considerably improve differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…1(b) by the numbered circles. More details concerning the environment can be found in [11]. The Rx positions have been selected to cover various configurations, i.e.…”
Section: A Geometrical Configurationmentioning
confidence: 99%
See 3 more Smart Citations
“…1(b) by the numbered circles. More details concerning the environment can be found in [11]. The Rx positions have been selected to cover various configurations, i.e.…”
Section: A Geometrical Configurationmentioning
confidence: 99%
“…Nonetheless, massive MIMO measurements in industrial scenarios are quite scarce. In a previous work [11], polarimetric channel measurements of a Multi-User (MU) Multiple-Input Single-Output (MISO) setup for an indoor industrial scenario are presented. The center frequency and the bandwidth of analysis are equal to 3.5 GHz and 80 MHz, respectively, the number of array elements being 100.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…F. Challita et al [ 14 ] have investigated the performance of PD for a massive MIMO system in industrial environment to address the problem of cross-polarization discrimination. F. Challita et al [ 15 ] have reported significant improvement in spectral efficiency in PD based massive MIMO system for Industry 4.0 applications. There is a gap, however, in existing literature on exploring PD for M2M and industrial communication.…”
Section: Introductionmentioning
confidence: 99%